1991
DOI: 10.1128/jvi.65.9.4832-4838.1991
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of two immunodominant domains of gp41, the transmembrane protein of human immunodeficiency virus type 1, using ten human monoclonal antibodies

Abstract: Immunogenic regions of the gp4l transmembrane protein of human immunodeficiency virus type 1 (HIV-1) were previously mapped by examining polyclonal sera from HIV-infected patients and rodent polyclonal and monoclonal antibodies (MAbs) to peptides of gp4l. To define the epitopes within these regions to which infected humans respond during the course of infection, the specificity of human MAbs to these regions had to be studied. Using 10 human MAbs identffied initially by their reactivity to whole gp4l in HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(97 citation statements)
references
References 34 publications
6
90
0
1
Order By: Relevance
“…Several human monoclonal antibodies specific for gp41 have been produced, and several epitopes within gp41 have been defined 27,30,31 (FIG. 3, TABLE 1 and BOX 1).…”
Section: Antibodies To Epitopes In Gp41mentioning
confidence: 99%
See 1 more Smart Citation
“…Several human monoclonal antibodies specific for gp41 have been produced, and several epitopes within gp41 have been defined 27,30,31 (FIG. 3, TABLE 1 and BOX 1).…”
Section: Antibodies To Epitopes In Gp41mentioning
confidence: 99%
“…A human monoclonal antibody, clone 3, to an epitope that spans the disulphide bond in the IMMUNODOMINANT loop of the ectodomain of gp41 (GCSGKLICTT) has also been shown to neutralize primary isolates 43,44 . Interestingly, human monoclonal antibodies (such as monoclonal antibody 246) that recognize epitopes that are offset by 5-7 amino acids upstream of the clone 3 epitope do not have this neutralizing capacity 30,45 .…”
Section: • V3 Loop: a Semi-conserved Region Of Gp120 That Is Structurmentioning
confidence: 99%
“…Next, the PFIs were probed with 126-7, a human mAb (an IgG2 version of 126-6) that only recognizes a trimeric conformation of gp41 shared between both pre-and post-fusion state (Gorny et al, 1989;Robinson et al, 1991 ;Tyler et al, 1990 ;Xu et al, 1991 ;Yuan et al, 2009 ). It recognizes residues from 641 to 648 in the cluster II of gp41.…”
Section: Biochemical and Antigenic Properties Of Pfismentioning
confidence: 99%
“…6-helix and 5-helix bundle proteins (Root et al, 2001) were kindly provided by Dr. Michael Root of Thomas Jefferson University. The following reagents were obtained through the NIH ARRRP: HIV-Ig from NABI and NHLBL; HIV-1 M group consensus envelope overlapping peptides (Cat #9487), HIV-1 IIIB N36 and C34 Peptides ( (Gallo et al, 2004); Cat #9822 and 9824, respectively) from DAIDS; mAb 98-6 (Gorny et al, 1989;Robinson et al, 1991;Tyler et al, 1990;Xu et al, 1991) from Dr. Susan Zolla-Pazner. SARS-CoV S protein peptide (PFYSNVTGFH-TINHTF; Cat #9605) was obtained through the NIH Biodefense and Emerging Infections Research Resources Repository.…”
Section: Elisamentioning
confidence: 99%
“…To date, most efforts to express soluble forms of gp41 have been limited to small fragments of the protein, including the heptad repeat (HR) regions (Root et al, 2001), the immunodominant loop between HR1 and HR2 known as cluster I (Gnann et al, 1987), a region between HR2 and the 2F5 epitope known as cluster II (Binley et al, 1996;Goudsmit et al, 1990;Xu et al, 1991), and the MPER (Luo et al, 2006;Opalka et al, 2004). Although Scholz et al (Scholz et al, 2005) have reported generating a larger 146 amino acid gp41 fragment (residues 536-681) fused to E. coli chaperone SlyD and showed its immunoreactivity with HIV-1 patient sera, no other immunoprobing was performed using mAbs to confirm antigenic integrity of the protein.…”
Section: Introductionmentioning
confidence: 99%